Layanan Konseling Karir “Trait and Factor” sebagai Upaya Meningkatkan Perencanaan Karir Siswa di Madrasah Aliyah - Muhimmatul Hasanah; Nurul ‘Ain Hidayah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
A lack of understanding of career planning among students is often a major factor contributing to confusion in selecting higher education majors or determining future employment pathways after graduating from madrasah. This issue is also evident at Madrasah Aliyah Ma’arif 7 Sunan Drajat Lamongan, where several students still lack clear and well-structured career plans. This study aims to describe the implementation of career counseling services based on the Trait and Factor approach as a strategic effort to enhance students’ career planning. The study employed a qualitative descriptive method using a case study design. Data were collected through observation, in-depth interviews, documentation, and a career planning scale questionnaire. The research participants consisted of eight twelfth-grade students selected purposively. The findings reveal that Trait and Factor-based counseling services were effective in increasing students’ self-awareness, clarifying their academic and career directions, and promoting rational decision-making aligned with their individual characteristics. The counseling process, comprising the stages of analysis, synthesis, diagnosis, prognosis, treatment, and follow-up had a positive impact on students’ readiness to design their future career paths. These results confirm that the Trait and Factor approach can be effectively adapted within madrasah-based career guidance services as a strategic framework for fostering students’ independence and maturity in career planning.